PENGARUH TERAPI BERMAIN MENGGUNTING DAN MENEMPEL KERTAS TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK PRASEKOLAH DI TK AL-HIDAYAH CURAH KALAK KABUPATEN SITUBONDO - Rochma, Prieta Lufiah Puteri; Munir, Zainal; Dewi, Novela Eka Candra; Nugroho, Setiyo Adi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Fine motor development is a crucial aspect for preschool children, yet not all children progress at the same rate. Despite its importance, the appropriate methods for stimulating this development are not well understood. This study aims to analyze the impact of cutting and pasting play therapy on the fine motor development of preschool children at TK Al-Hidayah Curah Kalak, Situbondo Regency. This research employed a quasi-experimental design with a pretest-posttest format and no control group. The sample consisted of 40 children selected through total sampling. Data analysis was conducted using the Wilcoxon Signed Rank test to evaluate differences before and after the intervention. Before the intervention, 75% of children were classified as "Suspect" in the cutting activity, and 77.5% were classified as "Suspect" in the pasting activity. After the intervention, 85% of the children reached the "Normal" category in the cutting activity, and 90% in the pasting activity. The Wilcoxon test results showed a p-value of 0.000, indicating a significant effect of the play therapy on improving the children's fine motor skills. Cutting and pasting play therapy significantly enhanced the fine motor development of preschool children at TK Al-Hidayah Curah Kalak, Situbondo Regency.